Initial-state, mean-free-path, and skin-depth dependence of attosecond time-resolved IR-streaked XUV photoemission from single-crystalline magnesium - Liao, Q.; Thumm, U. (My University, 2014)
We analyze the dependence of attosecond streaked photoelectron spectra and photoemission time delays from valence band (VB) and 2p core-level (CL) states of a single-crystalline Mg(0001) thin film on the (i) modeling of the substrate electronic structure, (ii) electron mean free path (MFP), (iii) screening of the near-infrared (NIR) streaking laser field, and (iv) chirp of the attosecond extreme ultraviolet (XUV) pulse. Our quantum-mechanical numerical simulations predict streaked photoemission spectra that depend sensitively on the XUV chirp and weakly on the screening of the streaking laser field by the substrate. They furthermore show that streaking time delays for VB emission are relatively insensitive to the modeling of the initial quantum states, electron MFP, and NIR skin depth of the Mg substrate, in contrast to the stronger dependence of streaking time delays for 2p CL emission on these factors.